From resource circularity policies to the zero-waste strategy - Adolfo F. L. Baratta (Agathón)
Over the last twenty years, waste management policies were aimed to mitigate environmental impacts; but in most cases the results of these policies had been the downcycling. The upcycling and the transition to circularity are good solutions to remedy the impacts of linear patterns of production and consumption. However, the only way to reduce environmental pressure is not through recycling but through reusing and avoiding waste production. In this direction, designers could play a significant role thanks to strategies such as those of Design for Longevity and Design for Deconstruction. Even if there are still few decision-making tools to support an effective evaluation of waste in the design phase, the above-mentioned strategies could lead designers towards a Zero Waste Strategy.